Core/shell quantum dots in ferroelectric liquid crystals matrix: effect of spontaneous polarisation coupling with dopant. Issue 7 (27th May 2016) - Pandey, Shivani; Vimal, Tripti; Singh, Dharmendra Pratap; Gupta, Swadesh Kumar; Pathak, Govind; Katiyar, Rohit; Manohar, Rajiv
ABSTRACT: In order to fabricate efficient and superior performance liquid crystal (LC) devices, the physical parameters of the LC mesogens can be duly altered by incorporating non-mesogenic materials like quantum dots (QDs), graphene and polymers. In the present work, the effect of adding core/shell QDs in two ferroelectric liquid crystals (FLCs), along with the change in their physical properties, has been investigated. A small concentration of QDs is dispersed into the two FLCs and temperature variations of vital parameters like spontaneous polarisation ( P s ), rotational viscosity, response time, relative permittivity and relaxation strength have been measured for both the FLC materials. The contrast ratio, UV–near visible absorbance as well as photoluminescence (PL) of both the mesogens have also been determined and compared. A faster electro-optical response and the induced phenomenon of PL with a temperature-dependent low-frequency relaxation mode have been observed in Felix 17/100 after the addition of QDs. The present study also provides valuable information about the interaction between QDs and the two FLC systems depending upon polarisation–field (P–E) coupling. The same dopant can interact with FLCs in dissimilar fashion if the intrinsic properties of both the FLCs are different thereby producing different modifications in their respective physical parameters. GRAPHICAL ABSTRACT: